Visitation to Urban Parks and Contributions to Health and Wellness - Altair Sancho-Pivoto; Sidnei Raimundo; Glauber Eduardo de Oliveira Santos (Ambiente & Sociedade, 2025)
Abstract Green areas such as parks are increasingly important in cities, by contributing to the maintenance of air quality, thermal balance and providing aesthetic values and balanced environments, which provide opportunities for contact with nature and contribute to the improvement of health and well-being of populations. Inspired by this context, the present work aims to investigate the perceptions of visitors to Ibirapuera Park (SP) about the motivations and benefits generated by visiting this urban green area, with special attention to the contributions to health and well-being. The methodological procedures of this investigation, of a qualitative and quantitative nature, involved a bibliographic and documental survey, as well as the application of 197 structured questionnaires with Ibirapuera’s visitors. The results indicate that the main benefits perceived after the visit are psychological and emotional, followed by improvement in physical health and relaxation made possible by contact with nature.